2018
DOI: 10.3390/f9070385
|View full text |Cite
|
Sign up to set email alerts
|

Watersheds and Trees Fall Together: An Analysis of Intact Forested Watersheds in Southern Patagonia (41–56° S)

Abstract: While intact forests have intrinsic value in terms of conserving biodiversity, they are also important for associated ecosystem services of soil and water conservation, in addition to the biodiversity, function and geomorphology of stream and river ecosystems. In this latter context, the perspective of watershed is more relevant than forest patch, however we are unaware of any landscape assessments of intact forested watersheds (IFWs). We mapped the coverage of forested watersheds with limited intervention for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Temperate rainforests of southern South America occur along the western land-ocean margin, with a mean distance to the ocean of 250 km between 37 and 55 • S (Aravena et al, 2002;Astorga et al, 2018). South American temperate rainforests are under a strong oceanic influence, having high relative humidity and low temperature oscillation throughout the year.…”
Section: Introductionmentioning
confidence: 99%
“…Temperate rainforests of southern South America occur along the western land-ocean margin, with a mean distance to the ocean of 250 km between 37 and 55 • S (Aravena et al, 2002;Astorga et al, 2018). South American temperate rainforests are under a strong oceanic influence, having high relative humidity and low temperature oscillation throughout the year.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, using rivers like Puelo River as sentinels, several studies have reported anomalous events in fjords of northwestern Patagonia (e.g., surface hypoxia events, harmful algal blooms), mainly during severe droughts (Valle-Levinson et al, 2007;León-Muñoz et al, 2013Iriarte et al, 2017;Díaz et al, 2021). Although northern Patagonian basins have not yet been modified by irrigation channels or reservoirs and still maintain extensive little-degraded native forest cover (CONAF and UACH, 2014;Astorga et al, 2018), recent threats such as increased wildfires and their joint effect with climate change have not been evaluated hydrologically to date. Considering this context, here we evaluate the influence of climate and land cover trends on the freshwater inputs of the Puelo River Basin to the Reloncaví Fjord (41.5 • S; Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…This biogeographic context promotes high levels of endemism and diversity of species supporting key ecosystem services (Rozzi et al, 2012), such as climate regulation, carbon storage, freshwater provision, and cultural diversity heritage. The region has one of the most continuous forest covers (120,000 km 2 ) and the largest area of peatlands and wetlands (42,000 km 2 ) representing the main carbon sink and carbon storage source in the southern hemisphere contributing to climate change mitigation (Astorga et al, 2018; Mansilla et al, 2021; Ministerio del Medio Ambiente, 2020; Rozzi et al, 2012). It is a global freshwater reserve because of the presence of the world's third‐largest ice fields, and there is a rich diversity of cultures and languages represented in particular by distinctive rural cultures and indigenous populations (Aylwin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%